2012
DOI: 10.1002/ejoc.201200515
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of p‐Sulfonatocalixarenes with Local Anaesthetics Guests: Binding Structures, Stabilities, and Thermodynamic Origins

Abstract: The binding geometries, abilities and thermodynamic parameters for the intermolecular complexation of three water‐soluble p‐sulfonatocalix[n]arenes (SCnAs), p‐sulfonatocalix[4]arene (SC4A), p‐sulfonatocalix[5]arene (SC5A), andp‐sulfonatothiacalix[4]arene (STC4A), with five local anesthetics (LA), procaine, tetracaine, lidocaine, dibucaine, and procainamide, have been determined by means of 1H NMR spectroscopy, X‐ray crystallography, and isothermal titration calorimetry (ITC). The obtained results show that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…It is gratifying to observe that the large influence of salts and buffers on the complexation of guests by SC4 has recently been increasingly acknowledged. For example, Guo, Liu, and co‐workers long conducted ITC measurements with SC4 in 0.1 M buffer concentration,15, 46, 47 but recently abandoned this routine practice and now use neutralization with base rather than (or in addition to) 0.1 M phosphate buffer to minimize competitive binding by addition of alkali metal ions 47. 60 The importance of avoiding buffers in titration experiments with SC4 was also recently emphasized by Biczók and co‐workers58 and Hof and co‐workers 61…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is gratifying to observe that the large influence of salts and buffers on the complexation of guests by SC4 has recently been increasingly acknowledged. For example, Guo, Liu, and co‐workers long conducted ITC measurements with SC4 in 0.1 M buffer concentration,15, 46, 47 but recently abandoned this routine practice and now use neutralization with base rather than (or in addition to) 0.1 M phosphate buffer to minimize competitive binding by addition of alkali metal ions 47. 60 The importance of avoiding buffers in titration experiments with SC4 was also recently emphasized by Biczók and co‐workers58 and Hof and co‐workers 61…”
Section: Resultsmentioning
confidence: 99%
“…Despite early NMR spectroscopic indications that alkali metal ions bind with SC4 because they affected the coalescence temperature at high concentrations at pH 8.9 (2.2 m NaCl), [7] it soon become common practice, which persists in part to date, to assess binding constants of guests with SC4 in 0.1 m sodium phosphate buffer solutions. [8][9][10][11][12][13][14][15] Although it was noted that "buffering cannot be used here since CX (SC4) are all capable to interact strongly with many buffers", [16] it was also concluded that "In fact, the (sodium) phosphate buffer (10 mm) has no influence on complexation." [17] Unsurprisingly, in view of this uncertainty, efforts were subsequently made to study the binding of cations by sensitive methods, particularly isothermal titration calorimetry (ITC).…”
Section: Introductionmentioning
confidence: 99%
“…The binding abilities of sodium salts of 123 and 124 with five local anesthetic drugs have been studied by another research group in both, solid state and in solution with revealing of interaction mechanism for each guest–host system (Table ).…”
Section: Inclusion Complexes Of Aminocalix[n]arenesmentioning
confidence: 99%
“…AFM is practical for measuring the surface properties such as morphology and the mechanical properties of many materials at the nanoscale level [19][20][21], and the technique has become viable to study soft matter especially polymers [22][23][24][25]. Height imaging is a widely used application of AFM in the scientific area, which can be utilized to analyze the morphologies of characterized nano-materials, such as nano-particles [26], nano-tubes [27], and nano-sheets [28].…”
Section: Introductionmentioning
confidence: 99%